PENGARUH KUALITAS DIPA DAN AKURASI PERENCANAAN KAS TERHADAP KUALITAS PENYERAPAN ANGGARAN PADA SATKER WILAYAH KPPN MALANG - Ratih Seftianova; Helmy Adam (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2013)
This research is purposed to analyze the influence of quality of DIPA (Budget Implementation Document) and the accuracy of cash forecasting to budget absorption quality of working unit in the KPPN Malang's working area. This research is a survey research which was conducted by distributing questionnairies and collecting secondary data. The questionnaire was distributed to every financial functionary and staf at working unit in the KPPN Malang’s working area. While, secondary data was obtained from the acts and reports of KPPN Malang. Working unit in the KPPN Malang’s working area was sampled by simplerandom sampling method to get high level of generalizability of all the population. Hypotheses testing used multiple regression analysis. The result of research shows that quality of DIPA positively affects to the budget absorption quality either from the level of budget absorption or proporsionality of budget absorption inter period. While, accuracy of cash forecasting does not affect budget absorption quality either from the level of budget absorption or proporsionality of budget absorption inter period.